Delay-Dependent Robust L2-L∞ Filtering for a Class of Fuzzy Stochastic Systems - Ze Li; Xinhao Yang (Abstract and Applied Analysis)
This paper is concerned with the L2-L∞ filtering problem for a kind of Takagi-Sugeno (T-S) fuzzy stochastic system with time-varying delay and parameter uncertainties. Parameter uncertainties in the system are assumed to satisfy global Lipschitz conditions. And the attention of this paper is focused on the stochastically mean-square stability of the filtering error system, and the L2-L∞ performance level of the output error with the disturbance input. The method designed for the delay-dependent filter is developed based on linear matrix inequalities. Finally, the effectiveness of the proposed method is substantiated with an illustrative example.